2012
DOI: 10.3991/ijoe.v8i3.2113
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Virtual Lab Module for Understanding the Concepts of Electric and Magnetic Field Patterns in Rectangular Waveguides and Cavities

Abstract: Abstract-Adopting standard-based weblab infrastructures can be an added value for spreading their influence and acceptance in education. This paper suggests a solution based on the IEEE1451.0 Std. and FPGA technology for creating reconfigurable weblab infrastructures using Instruments and Modules (I&Ms) described through standard Hardware Description Language (HDL) files. It describes a methodology for creating and binding I&Ms into an IEEE1451-module embedded in a FPGA-based board able to be remotely controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…Likewise, the electrical engineering education and electrical engineering study programs reached effectivenesses of 86.6% and 83.8%, respectively. The results of this study were in line with the research of Tatli and Ayas [10], which confirmed that virtual laboratories could solve the issues of basic chemistry practicums; Murniza's research [16], in biology through the VLab-Bio application; and Gupta's research [17], in the field of a virtual lab module for concepts of electric and magnetic fields. Thus, the results of this study proved that Virtual Labs could be a solution to the problem of the absence of basic laboratory practicum in the fields of science and technology due to limited facilities or other obstacles, such as the COVID-19 pandemic.…”
Section: Figure 4 Feasibility Of the Virtual Labs Modulesupporting
confidence: 82%
See 1 more Smart Citation
“…Likewise, the electrical engineering education and electrical engineering study programs reached effectivenesses of 86.6% and 83.8%, respectively. The results of this study were in line with the research of Tatli and Ayas [10], which confirmed that virtual laboratories could solve the issues of basic chemistry practicums; Murniza's research [16], in biology through the VLab-Bio application; and Gupta's research [17], in the field of a virtual lab module for concepts of electric and magnetic fields. Thus, the results of this study proved that Virtual Labs could be a solution to the problem of the absence of basic laboratory practicum in the fields of science and technology due to limited facilities or other obstacles, such as the COVID-19 pandemic.…”
Section: Figure 4 Feasibility Of the Virtual Labs Modulesupporting
confidence: 82%
“…The selection of Virtual Labs as a solution to this problem is based on the results of needs analysis and a literature review providing research results and previous best practices. Many studies have proven that virtual laboratories are effective for practical learning in various subjects such as physics [5]; [15], chemistry [10], biology [16], magnetism [17], basic electronics [7], computers [18], engineering education [14], [19]. The results of these studies have proven that virtual laboratories have many advantages, so it is considered appropriate to solve the problem of the absence of laboratory practicums that resulted in students' low learning outcomes.…”
Section: Theoretical Studymentioning
confidence: 99%
“…The learning process toward mastering the concept of the protection system must be supported and facilitated by the appropriate resources. The concept of electrical energy is abstract and therefore students require the appropriate learning media to understand this topic [11], [12]. Using learning multimedia, such as videos, animations, simulations, augmented reality, and virtual reality, is essential to improving learning outcomes [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salienta-se ainda que existem programas similares na literatura, tais como [8][9][10]. Kumar [8] apresentou um código capaz de ilustrar os campos elétricos e magnéticos para qualquer modo TE ou TM, de qualquer ordem, em um guia retangular, considerando todas as vistas do dispositivo.…”
Section: Introductionunclassified
“…Através do programa, é possível alterar parâmetros de entrada, selecionar o método de solução, especificar o número de modos, raios e reflexões. Já Gupta et al [10] exibem um trabalho similar ao proposto neste artigo. Através do LabVIEW, uma ferramenta de desenvolvimento da National Instruments, foi proposto um módulo de simulação com o intuito de visualizar os diversos padrões de campos eletromagnéticos dentro de um guia de onda retangular e de uma cavidade ressonante.…”
Section: Introductionunclassified